The Disconnect Between Education and Social Opportunity for the Formerly Incarcerated - Pryor, Marie (American journal of criminal justice, 2013)
This article aims to identify barriers associated with correctional education’s ability to produce social opportunity for the formerly incarcerated. This qualitative review of data collected in the Midwestern and Northeastern parts of the United States serves to better inform the literature surrounding correctional education, as to its positive and negative attributes, and sheds light on areas in which systematic improvements can be made. The goal of these independent but related studies is to investigate correctional education’s role in the outcomes of reentry experiences of former prisoners with emphasis on employment and educational opportunities, including the effects of race on prisoner and staff attitudes toward correctional education. This article serves to inform policy and future research in regards to correctional education, mainly in its uses, implementations, and outcomes.